1999
DOI: 10.1023/a:1026679430553
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: CT can measure absolute hepatic arterial and portal venous perfusion; pilot data suggests these are raised and lowered, respectively, in cirrhosis. This study examined the value of functional CT in assessing cirrhosis, using the prothrombin ratio (PTR) as a marker for hepatic parenchymal damage. Twenty subjects with viral-induced cirrhosis (11 men and 9 women; 55.41 +/- 7.86 years) and 14 controls (8 men and 6 women; 48.36 +/- 17.67 years) were studied. A single section through the liver was scanned after bolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In this study, we observed increased HAP and decreased HPP in the precancerous lesions group. This is similar to the result reported by Tsushima et al [36], in which the rise of HAP compensates the decrease in HPP and the increase in HAP is often less than the decrease in HPP. …”
Section: Discussionsupporting
confidence: 91%
“…In this study, we observed increased HAP and decreased HPP in the precancerous lesions group. This is similar to the result reported by Tsushima et al [36], in which the rise of HAP compensates the decrease in HPP and the increase in HAP is often less than the decrease in HPP. …”
Section: Discussionsupporting
confidence: 91%